(untitled) (American Journal of Multidisciplinary Research and Innovation, 2022)
The teaching profession remains challenging due to growing demands and the world’s changing needs. However, the role of teachers has remained inspiring, requiring more service than employment for the sake of the youth and future generations. The study aimed to assess the extent of awareness of the current trends and the commitment in the teaching profession of public school teachers in the Schools Division of Antique, Philippines. The researchers employed a descriptive-correlational research design using a validated questionnaire in data gathering for the 320 randomly chosen teacher-respondents. Results revealed that most of the teachers were degree holders only, with less than ten years of teaching experience, and were dominated by female teachers. They were highly aware of the current trends and practices in the teaching profession and highly committed to their work. Results also indicated that teachers’ commitment is influenced by their level of education. Teachers with a greater level of education are more committed to their careers. Teachers with higher educational attainment are more effective than those with a lesser level of education. Similarly, teachers with more years of experience teach better than those with less experience. Teachers’ educational level and sex have little effect on their teaching performance. Moreover, teachers’ performance is related to their understanding of current trends and practices in the teaching profession and their commitment. Therefore, the greater teachers’ awareness, the more receptive they are to change, and the greater their commitment, the better their teaching performance and the tasks and responsibilities they may be assigned in response to changes in the educational system. The researchers suggest that the department shall provide continuous professional development interventions to give educators the tools and skills to stay modern with the needs of students and allows them to plan for changing trends in education.